2017
DOI: 10.1007/s00299-017-2126-z
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis ORANGE (AtOR) gene promotes carotenoid accumulation in transgenic corn hybrids derived from parental lines with limited carotenoid pools

Abstract: The AtOR gene enhances carotenoid levels in corn by promoting the formation of plastoglobuli when the carotenoid pool is limited, but has no further effect when carotenoids are already abundant. The cauliflower orange (or) gene mutation influences carotenoid accumulation in plants by promoting the transition of proplastids into chromoplasts, thus creating intracellular storage compartments that act as metabolic sink. We overexpressed the Arabidopsis OR gene under the control of the endosperm-specific wheat LMW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…ORANGE has been shown as an important genetic tool for carotenoid enhancement in plants (Sun et al ., ; Yuan et al ., 2015b). Ectopic expression of a wild‐type OR leads to carotenoid accumulation in grains of rice and maize (Bai et al ., ; Berman et al ., ), in purple‐fleshed sweetpotato (Park et al ., ) and in calli of sweetpotato and Arabidopsis (Kim et al ., ; Yuan et al ., 2015a). The ‘golden SNP’ in OR is the cause for β‐carotene accumulation in melon fruit (Tzuri et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…ORANGE has been shown as an important genetic tool for carotenoid enhancement in plants (Sun et al ., ; Yuan et al ., 2015b). Ectopic expression of a wild‐type OR leads to carotenoid accumulation in grains of rice and maize (Bai et al ., ; Berman et al ., ), in purple‐fleshed sweetpotato (Park et al ., ) and in calli of sweetpotato and Arabidopsis (Kim et al ., ; Yuan et al ., 2015a). The ‘golden SNP’ in OR is the cause for β‐carotene accumulation in melon fruit (Tzuri et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that the overexpression of the Or gene can affect the endogenous carotenoid synthesis genes (Bai et al, 2014(Bai et al, , 2016Goo et al, 2015), while other studies showed that the overexpression of the Or gene stimulates accumulation of carotenoids without an effect on endogenous carotenoid synthesis genes (Yuan et al, 2015;Zhou et al, 2015). Recently, Berman et al (2017) showed that the overexpression of the Or gene depends on the level and composition of carotenoid of the wild-type plants. It was reported that the AtOr gene can enhance carotenoid levels by promoting the formation of carotenoid-sequestering structures when the carotenoid pool is limited, but has no further effect when carotenoids are already abundant (Berman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Berman et al (2017) showed that the overexpression of the Or gene depends on the level and composition of carotenoid of the wild-type plants. It was reported that the AtOr gene can enhance carotenoid levels by promoting the formation of carotenoid-sequestering structures when the carotenoid pool is limited, but has no further effect when carotenoids are already abundant (Berman et al, 2017). Our results showed that in all transgenic plants derived from wildtype maize with less carotenoid content (H145-WT), the content of both total carotenoids and β-carotene was higher than in transgenic plants from wild-type maize with more carotenoid content (H95-WT).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations